Retirement claims of members of the security forces in the Czech Republic - Kavan, Štěpán; Kavan, Štěpán (Vysoká škola evropských a regionálních studií, 2020)
The thesis deals with the retirement claims of members of the security forces in the Czech Republic in accordance with the legislative definition of Act No. 361/2003 Coll., On the employment of members of the security forces, as amended and compared with previous legislation by Act No. 186/1992 Coll. , on the employment of members of the Police of the Czech Republic, as amended. The goal of the state is to maintain the stability of the security forces, to which the issue of retirement claims is tied. Due to the nature and complexity of the profession of the security corps, its conditions, activities, risks and demands, the state has an obligation to motivate members of the security forces in a certain way to remain in the employment relationship for as long as possible. One of the motivations is the provision of retirement entitlements.
Výsluhové nároky příslušníků bezpečnostních sborů v České republice
Keywords: Security forces, retirement claims, severance pay, member; Bezpečnostní sbory, výsluhové nároky, odchodné, příslušník